The Closing Door: The Effect of Race on Charter School Closures. (August 2017) - Paino, Maria; Boylan, Rebecca L.; Renzulli, Linda A.
Charter schools are promoted by policy makers and advocates as a way to reduce educational inequality. Charter schools tend to enroll higher proportions of black students than do traditional public schools. However, the accountability function of charter schools means that these schools are also more likely to close than traditional public schools. A high incidence of closure can lead to educational instability with students moving in and out of charter schools and traditional schools. We use critical race theory to build on prior work, examining the factors that may promote or constrain charter school closure. Specifically, we ask, how do the racial demographics of a charter school affect its likelihood of closure? Our findings reveal that as the proportion of black students in a charter school increases, so too does its likelihood of closings. Our work suggests that the promotion of charter schools as avenues of racial equity may be misleading.